PENGEMBANGAN INSTRUMEN SOAL CERITA OPEN ENDED PADA MATERI BILANGAN CACAH UNTUK MENGUKUR KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV SEKOLAH DASAR - Silvia Maharani; Alvin Muhammad Fauzi; Syifa Faza Salsabila; Tiara Denta Natsyah; Dwiky Nurfauzi; Hafiziani Eka Putri; Teten Ginanjar Rahayu (LPPM Universitas Cipta Mandiri, 2026)
Elementary school students' mathematical problem-solving ability in solving mathematical word problems is still relatively low. This study aims to develop an open-ended word problem instrument on integers to measure the problem-solving ability of fourth-grade elementary school students that is valid, reliable, and suitable for use as a learning evaluation tool. This study used the Research and Development (R&D) method with a 4-D model that includes the stages of Define, Design, Develop, and Disseminate. The research subjects consisted of 28 fourth-grade elementary school students in one of the schools in Bekasi City. Data collection techniques were carried out through expert validation and limited trials. The results showed that all items obtained valid and very valid categories with a reliability value of 0.80 in the very strong category. The results of the difficulty level test showed that all items were in the moderate category, while the results of the discrimination test were in the good to very good category. In addition, the results of the trial showed that students were able to use various problem-solving strategies in solving open-ended problems according to Polya's problem-solving stages. Thus, the developed open-ended word problem instrument was declared valid, reliable, and suitable for use in measuring elementary school students' mathematical problem-solving abilities.